Role of Pokdarwis in Assistance of Tourism Village Community Empowermen in Dongde Valley - Erna Wigati; Pontianus Kuswiyata (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
This article is to find out the role of Pokdarwis in assisting the empowerment of tourism villages in terms of supporting and inhibiting factors and their impact on the Dongde Valley tourism village 2020. The method used is a qualitative method by being directly involved in mentoring and conducting observations, observations and interviews with Pokdarwis administrators with the aim of knowing the role, supporting and inhibiting factors as well as the impact of the role of Pokdarwis in empowerment assistance in the Dongde Valley Tourism Village. The result of this article is to make the village community have the same view of turning their village into a tourist village that empowers community members to be more advanced and become a global tourist village with the awareness of citizens in raising funds to finance the needs of their village with joint contributions and seeking CSR or assistance to other parties. Outsiders realize a tourist village can support the limited human resources and funds for community empowerment. The role of Pokdarwis makes Human resources in the Dongde Valley tourist village have skills and become confident in empowering the community in the tourist village